Modalities of causal relations established by elementary school students based on the reading of a text with historical content (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2023)
This study aimed to analyze the ways in which sixth-grade elementary school students reflected on historical causality through the establishment of relationships resulting from a reading activity. A qualitative exploratory study was conducted involving nine sixth-grade students from Guanajuato, Mexico. Individual interviews were conducted using a semi-structured interview protocol aimed at delving into the causal interpretations suggested by the students. The results revealed six modalities of causal relationship, four of which contained temporal features, one contained semantic and pragmatic elements, and one was constructed considering the placement of events in the text. The narrative and discursive aspects of the causal relationships established by the students are discussed, as well as some reflections on approaching history through reading texts.
Keywords: historical thinking; relation; causality; reading